Total Synthesis of the Natural Pyridocoumarins Goniothaline A and B - Ahn, Sungwan; Yoon, Jeong A; Han, Young Taek (Synthesis, 2019)
In this paper, we report the first total synthesis of goniothaline A and B, which are rare natural pyridocoumarins isolated from Goniothalamus australis. The key feature of the synthesis of goniothaline A is high-yielding silver-catalyzed cycloisomerization to afford the pyridine moiety. In addition, goniothaline B, a natural 8-hydroxyquinoline derivative, is readily synthesized by the regioselective demethylation of goniothaline A.
Keywords: total synthesis; goniothaline; Perkin reaction; silver-catalyzed cycloisomerization; selective demethylation